Suicide or Lynching? The Death of Frederick Jermaine Carter. - Stephen, Curtis (Crisis (15591573))
The article discusses the death of Frederick Jermaine Carter, a 26-year-old Black man who lived in Sunflower, Mississippi. Carter was found hanging from a tree in the predominantly White area of Greenwood, Mississippi in December 2010 after his disappearance from Sunflower. The Leflore County coroner's preliminary report which suggests he committed suicide is being contested by people who think Carter was lynched.